Map showing wooded and prairie tracts in part of northern Alberta and portions of the districts of Assiniboia and Saskatchewan - Tyrrell, Joseph Burr, 1858-1957 (Surveyor); Geological and Natural History Survey of Canada (The Burland Lith. Co., 1887)
This is a map of Northern Alberta and Saskatchewan in 1887, showing wooded and prairie regions and trails. Includes notes on vegetation species, soil type and condition, rivers, streams and lakes. Scale 1:506,880. Relief shown by contours, hachures, and spot heights. Shows fully and partially wooded regions, wooded river valleys, prairies and trails. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .